2014
DOI: 10.1080/15374416.2013.873979
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Development of Anxiety in Children With or Without Intellectual Disability

Abstract: Objective To examine group differences in presentation and trajectory of anxiety symptoms and disorders in children with moderate to borderline Intellectual Disability (ID) and children with typical cognitive development (TD). Method Examined anxiety disorders and symptoms in children with ID (n=74) or TD (n=116) annually from ages 5 through 9 using a parent structured interview and questionnaire. Logistic regression was used to examine odds of meeting anxiety criteria and hierarchical linear modeling was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 23 publications
(40 reference statements)
3
38
1
1
Order By: Relevance
“…Dekker and Koot (2003) found that twice as many children with ID and an anxiety disorder also met criteria for one or more co-occurring disruptive behavior disorders (42.5 %; i.e., ADHD, ODD, and conduct disorder), compared to typically developing children with anxiety disorders (20.6-20.9 %; e.g., Fleitlich-Bilyk and Goodman 2004). Green et al (2014) also found significantly higher odds of children with ID meeting clinical significance for both anxiety and inattentive/hyperactive symptoms, in particular, and externalizing problems, overall. These odds proved to be above chance levels (at least twice the frequency as expected by chance), given the higher rates of clinical levels of anxiety and other psychiatric symptoms in this population, and may result in higher levels of impairment among these children.…”
Section: Anxiety Disorders In Children With Iddmentioning
confidence: 81%
See 2 more Smart Citations
“…Dekker and Koot (2003) found that twice as many children with ID and an anxiety disorder also met criteria for one or more co-occurring disruptive behavior disorders (42.5 %; i.e., ADHD, ODD, and conduct disorder), compared to typically developing children with anxiety disorders (20.6-20.9 %; e.g., Fleitlich-Bilyk and Goodman 2004). Green et al (2014) also found significantly higher odds of children with ID meeting clinical significance for both anxiety and inattentive/hyperactive symptoms, in particular, and externalizing problems, overall. These odds proved to be above chance levels (at least twice the frequency as expected by chance), given the higher rates of clinical levels of anxiety and other psychiatric symptoms in this population, and may result in higher levels of impairment among these children.…”
Section: Anxiety Disorders In Children With Iddmentioning
confidence: 81%
“…However, later in childhood, children with TD and ID exhibit more comparable rates of separation anxiety. When analyzing parent reports of children's anxiety symptoms through written questionnaires, elementary-aged (i.e., 5-9 years) children with ID are more likely to fall within clinical levels of symptoms on the anxiety problems subscale of the Child Behavior Checklist (13.7-28.1 %) compared to children with typical development (6.0-14.8 %), with significant differences between the groups emerging by ages 8 and 9 (Green et al 2014). Additionally, anxiety levels appear to be related to children's level of cognitive functioning.…”
Section: Anxiety Disorders In Children With Iddmentioning
confidence: 98%
See 1 more Smart Citation
“…ADHD and anxiety comorbidities were found higher among individuals with DS-ID than in typically developed individuals [3,69].…”
Section: Anxiety Disordersmentioning
confidence: 94%
“…Studies suggest that 10-22% of the individuals with ID have met diagnostic criteria for anxiety disorder; this rate is higher than the individuals with typical development (3-7%). Studies have found no diference in prevalence of anxiety among mentally disabled individuals between the genders [69]. As in the general population, anxiety symptoms such as fear, trembling, lushing, and irritability can be observed in DS [9].…”
Section: Anxiety Disordersmentioning
confidence: 99%